Results from systematic screening for cardiovascular risk in outpatients with rheumatoid arthritis in accordance with the EULAR recommendations. Issue 11 (12th July 2013) - Primdahl, Jette; Clausen, Joan; Hørslev-Petersen, Kim
Abstract : Aim: To investigate risk factors for the development of cardiovascular disease (CVD) and estimate the risk of cardiovascular death in rheumatoid arthritis (RA) patients in accordance with EULAR recommendations. Materials and methods: Outpatients with RA ≤85 years of age from a Danish hospital were invited to participate. Patients' risk of cardiovascular death was calculated according to the SCORE system, based on total cholesterol/high-density lipoprotein (HDL) ratio, smoking habits, blood pressure, age and gender. The SCORE was adjusted based on disease duration, IgM-RF/anti-CCP positivity and the presence of extra-articular manifestations. Factors such as history of CVD, hypertension or diabetes mellitus (DM), fasting glucose, exercise habits, body mass index (BMI) and waist circumference were explored. Results: 836 patients participated; 71.5% women; mean (SD) age 64.3 years (12.0); 152 (19.1%) were already diagnosed with CVD and 74 (9.0%) with DM. Among the 644 patients without CVD or DM, 158 (24.5%) were smokers, 229 (35.8%) had a systolic blood pressure ≥140, 397 (65.6%) total cholesterol ≥5.0 mM/L, 326 (55.4%) low-density lipoprotein cholesterol ≥3.0 mM/L, 18 (4.0%) women and 19 (12.1%) men had a HDL-cholesterol level below 1.2/1.0 mM/L. BMI was >25 in 409 (63.8%). Waist circumference was above 80/94 cm in 297 (63.3%) of female and 111 (63.8%) of male patients, respectively, and 418 (64.9%) exercised ≤5 times a week. Among patients without DM, 14.3% had a fasting glucose ≥6.0 mmol/L. The SCORE was ≥5 in 122 (20.2%). They were referred to follow-up by their GP and community advice services. Conclusions: Systematic screening revealed several risk factors that needed medical follow-up or support to initiate lifestyle changes.